Development of Digital Comic Media on Atomic Structure Material for Grade X to Enhance Quality Education - Siti Fatma Ningrum; Fitriani; Dedeh Kurniasih (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop a digital comic as a learning medium for year 10 students on the topic of Atomic Structure, as a solution to the low interest and understanding among students regarding abstract chemistry concepts. The method used is Research and Development (R&D), based on a modified Borg and Gall model consisting of seven stages. The developed digital comic was validated by three experts-subject matter, media, and language-with validation scores of 92%, 87%, and 95% respectively, falling within the appropriate to highly appropriate category. Small-scale and large-scale trials were conducted with Year 10 students at SMA Taman Mulia, resulting in practicality scores of 74% and 84%, which indicate very positive responses to the media. The digital comic proved to be engaging, communicative, and effective in helping students understand the concept of atomic structure. Therefore, the digital comic is deemed suitable for use as an innovative alternative learning medium in chemistry lessons.